Determination of Fish Origin by Using 16S rDNA Fingerprinting of Microbial Communities by PCR-DGGE: An Application on Fish From Different Tropical Origins - Montet, Didier; Nguyen, Doan Duy Le; Kouakou, Amenan Clementine (IntechOpen, 2012)
None